2018
DOI: 10.1111/apt.14806
|View full text |Cite
|
Sign up to set email alerts
|

Serological markers of extracellular matrix remodeling predict transplant‐free survival in primary sclerosing cholangitis

Abstract: Extracellular matrix remodeling is elevated in primary sclerosing cholangitis patients compared to ulcerative colitis patients. Furthermore, the interstitial matrix marker PRO-C3 was identified as a potent prognostic marker and an independent predictor of transplant-free survival in primary sclerosing cholangitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 35 publications
5
36
1
Order By: Relevance
“…PRO‐C3 has been demonstrated to be highly related to fibrosis stage and disease activity across various CLD aetiologies . Within cross‐sectional NAFLD studies, PRO‐C3 was shown to perform well when separating patients with advanced fibrosis from those without (AUROC 0.81, 0.74) .…”
Section: The Clinical Utility Of Pro‐c3mentioning
confidence: 98%
See 3 more Smart Citations
“…PRO‐C3 has been demonstrated to be highly related to fibrosis stage and disease activity across various CLD aetiologies . Within cross‐sectional NAFLD studies, PRO‐C3 was shown to perform well when separating patients with advanced fibrosis from those without (AUROC 0.81, 0.74) .…”
Section: The Clinical Utility Of Pro‐c3mentioning
confidence: 98%
“…In both studies, significant changes in PRO‐C3 level from baseline were observed as a result of therapy . There are limited studies regarding the predictive value of PRO‐C3; however, studies have shown that PRO‐C3 has the ability to predict decompensation and mortality in patients with liver disease, and to predict transplant‐free survival in patients with PSC . However, further investigation regarding the predictive and prognostic value of PRO‐C3 is required, as well as its relationship to clinical outcomes.…”
Section: The Clinical Utility Of Pro‐c3mentioning
confidence: 99%
See 2 more Smart Citations
“…A specific marker of collagen III formation Associated with clinical outcome (LTX or death) in a single center study [193] Showed change at 12 weeks of treatment in a phase II study on NGM282, indicating dynamic potential [107] PRO-C3 directly reflects collagen III formation, which is an important part of fibrogenesis and hence the pathogenesis of PSC, and a therapeutic target…”
Section: Pro-c3 Fibrosismentioning
confidence: 99%